What effect does functional appliance treatment have on the temporomandibular joint? A systematic review with meta-analysis - Karma Shiba Kyburz; Theodore Eliades; Spyridon N. Papageorgiou (SpringerOpen, 2019)
Abstract Background The aim of the current systematic review was to compare the radiologic effects of functional appliance Class II treatment compared to no treatment on the temporomandibular joint and its components. Methods Nine databases were searched up to June 2019 for randomized or prospective non-randomized clinical trials comparing Class II patients treated with functional appliances to untreated patients. After duplicate study selection, data extraction, and risk of bias assessment with the Cochrane tool and the ROBINS-I tool, random effects meta-analyses of mean differences (MDs) and their 95% confidence intervals (CIs) were performed, followed by the assessment of the quality of evidence with GRADE. Results A total of 11 papers on 8 unique trials with 377 patients (39.8% male; average age 10.3 years) were finally included. Limited evidence indicated that compared to untreated growing patients functional appliance treatment was associated with increased condylar width (2 studies; MD 1.1 mm; 95% CI 0.1 to 2.2 mm; very low evidence quality), decreased anterior joint space (2 studies; MD − 0.7 mm; 95% CI − 0.5 to − 0.9 mm; very low evidence quality), increased superior joint space (2 studies; MD 0.7 mm; 95% CI 0.5 to 1.0 mm; very low evidence quality), increased posterior joint space (2 studies; MD 1.0 mm; 95% CI 0.9 to 1.2 mm; very low evidence quality), and vertical displacement of the glenoid fossa (2 studies; MD 0.4 mm; 95% CI 0.1 to 0.7 mm; very low evidence quality). The main limitations affecting the validity of the present findings were the inclusion of non-randomized studies with methodological issues, imprecision due to limited samples of the included studies, and inconsistencies among studies. Conclusions Currently existing evidence from controlled clinical studies on humans indicates that functional appliance treatment is associated with positional and skeletal alterations of the temporomandibular joint in the short term compared to untreated controls. However, the clinical relevance of these changes remains unclear, while the quality of existing evidence is low due to methodological issues of existing studies. Review registration PROSPERO, CRD42018109271